2011
DOI: 10.1176/appi.ap.35.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Motivational Interviewing Skills to Third-Year Psychiatry Clerkship Students

Abstract: students can gain basic knowledge and increased confidence in working with patients for promoting behavioral change, even with a brief session, taught by nonexperts in motivational interviewing theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
4
0
3
Order By: Relevance
“…A plethora of educational curricula focused on training medical students on smoking cessation techniques have been proposed and successfully implemented [9-11]. However, evidence shows that medical schools are not consistently preparing students to counsel patients on smoking cessation and that, despite the existence of model curricula, vast disparities persist in medical students’ knowledge of smoking-related health risks [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of educational curricula focused on training medical students on smoking cessation techniques have been proposed and successfully implemented [9-11]. However, evidence shows that medical schools are not consistently preparing students to counsel patients on smoking cessation and that, despite the existence of model curricula, vast disparities persist in medical students’ knowledge of smoking-related health risks [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Strategies such as MI have been broadly emphasized in the practical and clinical skills training of medical students and have been shown to enhance confidence and knowledge regarding approaches to behavioural intervention. 17 A combination of patientcentered counselling and evidence-based pharmacotherapies produces significantly increased abstinence rates when treating nicotine addictionand might usefully form the basis of SCC training in the pre-clerkship years. 6,7 Although the majority of Canadian institutions that participated in the curriculum survey claimed to promote knowledge of pharmacological interventions and employ one or more enhanced methods of learning including, but not limited to, CBL, PBL, TBL, PSD and SLMs, only three institutions completed any form of direct evaluation of clinical counselling skills using role-play or observed interaction with real or standardized patients.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of SBIRT training to residency programme has been shown to greatly improve counselling skills and confidence in these skills (Tetrault et al, 2011). It has also been demonstrated that knowledge and confidence in working with patients for promoting smoking cessation as well as other behavioural change can be improved by brief (1-2 hour) training sessions, including brief web-based intervention (Pederson, Blumenthal, Dever, & McGrady, 2006;Roman, Borges, & Morrison, 2011). Implementation of US Public Health Service guidelines for smoking cessation also is less than optimal.…”
Section: Discussionmentioning
confidence: 99%